Potential of Sewage Sludge from the Integrated Laboratory of UIN Sunan Gunung Djati Bandung as Organic Fertilizers Through Vermicomposting - Tri Cahyanto; Risda Arba Ulfa; Salsabila Qonita Kamelia; Musa’adah Musa’adah (Jurnal Biologi Tropis, 2022)
Sludge is a suspension of liquid waste and microorganisms originating from the Wastewater Treatment Plant (WWTP). The humus and nutrient content of sewage sludges can be used as compost by the vermicomposting mechanism. This study aims to determine the potential of sewage sludge in the Integrated Laboratory of UIN Sunan Gunung Djati Bandung as a raw material for making organic fertilizer through vermicomposting by utilizing the earthworm Eisenia fetida. The media containing a mixture of cow dung (CD) and sludge (S) was divided into four treatments consisting of Control (100% CD), P1 (75% CD + 25% S), P2 (50% CD + 50% S), and P3 (25% CD + 75% S) with the weight of each medium is 500 grams. A total of 20 adult earthworms (5-6 grams/20 heads) were added to each treatment medium for the vermicompost process for 8 weeks. The results showed that the composition of the media in treatment P1 showed the highest effect on the quality of vermicompost with percentages of C (42.62), N (1.85), P (1.21), and K (0.26) based on the SNI 7763-2018 standard. The conclusion of this study is that the sewage sludges from the Integrated Laboratory of UIN Sunan Gunung Djati Bandung can be used as raw material for making organic fertilizer with an optimum media composition of 75% CD + 25% S.